Holobiome Harmony: Linking Environmental Sustainability, Agriculture, and Human Health for a Thriving Planet and One Health - Gissel García; Martha Carlin; Raul de Jesus Cano (Microorganisms)
The holobiome is an interconnected network of microbial ecosystems spanning soil, plants, animals, humans, and the environment. Microbial interactions drive nutrient cycling, pathogen suppression, and climate regulation. Soil microbiomes facilitate carbon sequestration and enhance soil fertility, while marine microbiomes contribute to carbon capture and climate stability. However, industrial agriculture, extensive herbicide use, antibiotic overuse, and climate change threaten microbial diversity, leading to ecosystem and health disruptions. Probiotic interventions help to restore microbial balance. In human health, probiotics support gut microbiota diversity, reduce inflammation, and regulate metabolism. In agriculture, soil probiotics enhance microbial diversity, improve nutrient cycling, and degrade contaminants, increasing crop yields and soil health. Case studies show that microbial inoculants effectively remediate degraded soils and enhance nutrient uptake. Artificial intelligence is transforming microbiome research by enabling predictive modeling, precision probiotic design, and microbial consortia optimization. Interdisciplinary collaboration and supportive policies are essential for restoring microbial equilibria, ensuring ecosystem resilience, and promoting long-term sustainability. The integration of artificial intelligence, clinical research, and sustainable practices is crucial for advancing holobiome science. The holobiome framework underscores the need for interdisciplinary collaboration to address global challenges, bridging environmental sustainability, agriculture, and public health for a resilient future.